g={(-9, 0), (-3, 2), (2, -9), (5, 6)} ; h= ( x )= 2x + 9

Calculus
Tutor: None Selected Time limit: 1 Day

find the following:

g-1^(2)=

h-1^(x)=

(h ° h-1^) (1)=

Note: the -1^ is a negative one squared 

May 11th, 2015

You can ask back if you have any doubt. I am here.
May 11th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
May 11th, 2015
...
May 11th, 2015
Dec 9th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer